Intelligent splicing technology of off-axis aspheric mirrors based on Zygo interferometer. (January 2023) - Lan, Menghui; Li, Bing; Wu, Xiuyuan; Wei, Xiang
Highlights: A Zygo interferometer-based intelligent splicing technology for off-axis aspherical mirrors was proposed to provides a "small to big" manufacturing strategy for large aspherical mirrors. A Zygo interferometer, a splicing adjustment platform, and a computer-integrated algorithm were combined to achieve closed-loop adjustment of the off-axis aspherical mirrors. The splicing adjustment platform performs positional corrections to the to-be-adjusted off-axis aspherical mirrors using the calculated point cloud registration parameters as the adjustment amount. The iterative operation of point cloud alignment and splicing platform adjustment was done until the positional deviation of the adjusted off-axis aspherical mirror surface reaches a predetermined threshold value. Abstract: With the increasing size of the aspheric, manufacturing and testing technologies face enormous challenges. A Zygo interferometer-based intelligent splicing technology for off-axis aspherical mirrors is proposed in this paper, which provides a "small to big" manufacturing strategy for large aspherical mirrors. In the proposed method, a Zygo interferometer, a splicing adjustment platform, and a computer-integrated algorithm are combined to achieve closed-loop adjustment of the off-axis aspherical mirrors. Taking any one of the off-axis aspherical sub-mirrors as a reference, the point cloud information on the surfaces of all off-axis sub-mirrors is obtained by combining the optimal spherical wavefront data with the Zygo interferometer data. The splicing adjustment platform performs positional corrections to the to-be-adjusted off-axis aspherical mirrors using the calculated point cloud registration parameters as the adjustment amount. The iterative operation of point cloud alignment and splicing platform adjustment is done until the positional deviation of the adjusted off-axis aspherical mirror surface reaches a predetermined threshold value, at which point the adjustment stops. The experimental verification employed two off-axis aspherical sub-mirrors with a 100 mm aperture that belonged to the same aspherical surface. The result shows that large aspherical mirrors can be made quickly and effectively with intelligent splicing technology.